PENGARUH PROGRAM SIARAN ACARA PRO 2 GOES TO SCHOOL LEMBAGA PENYIARAN PUBLIK RADIO REPUBLIK INDONESIA TERHADAP KREATIVITAS PELAJAR DI SEKOLAH MENENGAH ATAS NEGERI 7 PEKANBARU - Dita Widia Pangestika; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Mass media plays an important role in providing both information and entertainment for public. The Radio Republic of Indonesia (RRI) Pro 2 88,4 FM, as one of the mass media which available in Pekanbaru, aired Pro 2 Goes To School program that expose talent and creativity of the students. The RRI also had an interactive dialogue which discuss various topics regarding activities and achievements of the schools in a fun and informative way. The objective of the study is to observe the effect of the Pro 2 Goes To School program on students creativity at SMA Negeri 7 Pekanbaru.The study used explanation quantitative methods. The data was collected by using Negeri 7 Pekanbaru with 565 students in total. In determining the size of the sample, slovin formula was applied and resulted in 85 samples. The proportional random sampling technique was used to select the respondents. To analyze the association between the variables, the researcher applied simple linear regression analysis by using statistical software, statistic product and service solution (SPSS) Windows version 16.Based on the simple linear regression analysis, the coefficient of the regression was Y = 22,051 + 0,765 X with significance level of 0,00 smaller than  = 0,05. The determination test resulted in 17,5%. The results suggested a low effect of Pro 2 Goes To School program on students creativity at SMA Negeri 7 Pekanbaru. The 82,5% was determined by other factors which were not observed in this study.